Attitude towards the Practice of Female Genital Cutting among School Boys and Girls in Somali and Harari Regions, Eastern Ethiopia - Asresash D. Abathun; Abdi A. Gele; Johanne Sundby (Obstetrics and Gynecology International)
Introduction. Female genital cutting (FGC) is a harmful traditional practice that violates women’s rights and threatens their health. Although much work has been done to tackle this practice in Ethiopia, the prevalence remains very high in Somali and Harari regions. This study aims to investigate the attitude towards FGC of young people (boys and girls) in Somali and Harari regions of Eastern Ethiopia. Methods. A cross-sectional quantitative study was carried out in Somali and Harari regions from October to December 2015. Two districts were purposely selected from the two regions, and a stratified random sampling technique was employed to select 480 subjects from the randomly selected schools. Results. Out of 480 questionnaires distributed, 478 (99.6%) respondents filled the questionnaires and returned them. The finding of the study reveals that 86% of study participants condemn the practice of FGC. Almost 59% of male participants from both study areas preferred to marry uncircumcised girls. Being a female and being a Muslim are significantly associated with the support toward the continuation of the FGC (P<0.05). Conclusion. Although the study demonstrates a positive attitude towards the abandonment of FGC, there is a need to increase the knowledge about the position of Islam in FGC and to educate women about the harmful effect of FGC.